Methodological foundations of project management based on a systematic approach - Rud , K (Ways to Improve Construction Efficiency, 2024)
The author`s research relates with identifying the causes of inefficient implementation of projects and their collapse. The research has shown that those approaches and methodologies that are offering today aren`t sufficiently based on theoretical knowledge. Attempts to solve effective project management are reduced to an attempt to neutralize problems that lie on the surface, and the inability to determine the root cause of ineffective project implementation pushes many scientists to develop new scientific directions, such as, for example, “leadership”, “flexible project management” or the search for new principles of management, which further deepens the already difficult situation which today takes place during the implementation of specific projects. So, for example, the inability to solve the issue of effective project implementation due to the formation of a theoretically grounded methodology is often “solved” by finding an effective manager – a “leader”, who eventually “burns out” at the workplace or his management is reduced to “aggressive management” or “usurpation of power” – another problem, and hence the direction of scientific research which has been discussed in many publications in recent years. For eliminating the existing problems that take place in project management, we have formed an effective project management methodology which based on a systematic approach. The proposed project management methodology makes it possible to form a holistic organizational structure of the project which simultaneously organically defines and synthesizes all types of resources that are necessary for project implementation. In addition, forming of the holistic organizational structure ensures its interaction with the surrounding environment, on which the project affects upon achieving of the goal. In this regard, are suggested that at the stage of determining the project`s goal to research its impact on the environment which relates with the project of a different levels of connections. This analyse gives an opportunity to determine feasibility of project implementation that gives to avoid various types of crises and disasters in the future.